THE USE OF PHOTOD YNAMIC THERAPY IN THE DOMESTIC ONCOLOGY. (REVIEW OF THE LITERA TURE) - V. V. Kuznetsov (Исследования и практика в медицине)
In this paper, it has been tasked to demonstrate progress is Russian scientists who are pioneers in the application of clinical photodynamic therapy (PDT) in Europe. In this review current understanding of the mechanisms of action PDT on the tumor and the body, the technical aspects of the application of the laser radiation of varying intensity, particularly its effect on biological tissues. The results of studies on the use of PDT with different photosensitizers in the complex therapeutic measures in patients with cancer. The data on the efficacy and safety of PDT. Given the effectiveness of PDT and ease of use, no adverse reactions, this medical technology can be attributed to one of the most promising trends in oncology. Accumulated a large experience of PDT in oncology testifies to high efficiency of this method in the treatment of various tumors. However, despite the positive results obtained in clinical practice, PDT in oncology is not widely used.It is proposed to implement this knowledge into the educational process at universities. Researchers of the А. Tsyb MRRC and Obninsk Institute for Nuclear Power Engineering (MEPhI) are working under development of educational complex program «Medical physics». This cooperation is expected to improve professional training and education in health physics.